Soil strength influences wheat root interactions with soil macropores. (30th October 2019) - Atkinson, Jonathan A.; Hawkesford, Malcolm J.; Whalley, William R.; Zhou, Hu; Mooney, Sacha J.
Abstract: Deep rooting is critical for access to water and nutrients found in subsoil. However, damage to soil structure and the natural increase in soil strength with depth, often impedes root penetration. Evidence suggests that roots use macropores (soil cavities greater than 75 μm) to bypass strong soil layers. If roots have to exploit structures, a key trait conferring deep rooting will be the ability to locate existing pore networks; a trait called trematotropism. In this study, artificial macropores were created in repacked soil columns at bulk densities of 1.6 g cm −3 and 1.2 g cm −3, representing compact and loose soil. Near isogenic lines of wheat, Rht‐B1a and Rht‐B1c, were planted and root–macropore interactions were visualized and quantified using X‐ray computed tomography. In compact soil, 68.8% of root–macropore interactions resulted in pore colonization, compared with 12.5% in loose soil. Changes in root growth trajectory following pore interaction were also quantified, with 21.0% of roots changing direction (±3°) in loose soil compared with 76.0% in compact soil. These results indicate that colonization of macropores is an important strategy of wheat roots in compacted subsoil. Management practices to reduce subsoil compaction and encourage macropore formation could offer significant advantage in helping wheat roots penetrate deeper into subsoil. Abstract : Root–macropore interactions were visualized and quantified using X‐ray CT. In compacted soil, 68.8% interactions resulted in pore colonization compared with 12.5% in loose soil. Results indicate that the colonization of macropores is an important strategy of roots to go through compacted subsoil in wheat.